Reversion free high-temperature vulcanization of cis-polybutadiene rubber with the accelerated-sulfur system - S. Gopi Sathi; R. Stocek; O. Kratina (eXPRESS Polymer Letters, 2020)
The vulcanization of high diene elastomers with conventional or semi-efficient vulcanization systems exhibit reversion at a higher temperature due to the breakage of the polysulfidic crosslinks established in the vulcanized network. As a result, the vulcanizate show inferior mechanical and thermal stability at elevated temperature. In this contest, the anti-reversion ability of Maleide F (75% N,N'-meta phenylene dimaleimide and a 25% blending agent: MF) was evaluated on the vulcanization behavior of cis-polybutadiene rubber (BR) with a conventional accelerated sulfur system. The anti-reversion ability of MF was also compared with Perkalink 900 (1,3-bis (citraconimidomethyl) benzene: PL). Based on the vulcanization studies using a moving die rheometer, it has been realized that MF forms carbon-carbon based bismaleimide crosslinks at the beginning of the vulcanization via Alder-Ene reaction. As a result, MF-filled systems exhibit a remarkable reversion resistance and a plateau type cure behavior even at 180 °C for a period of 1hr. On the other hand, PL shows its anti-reversion activity via Diels-Alder reaction after a short reversion. Moreover, the PL filled system exhibits a marching-modulus cure behavior at a higher vulcanization temperature. Therefore, PL cannot be considered as a promising candidate for the hightemperature vulcanization of BR with accelerated sulfur.